Financial Integration of the European Frontier Emerging Markets - Piljak, Vanja (My University, 2008)
This study investigates financial integration of the European frontier emerging markets. The purpose of the study is two-fold. First, the study investigates whether the European frontier emerging stock markets have become integrated into the world capital markets. As the second, the interdependences across the frontier emerging markets and their linkages to the three largest developed markets in Europe are examined. The sample includes five European frontier emerging markets (Croatia, Estonia, Romania, Slovakia and Slovenia) and the three largest developed markets in Europe (United Kingdom, France and Germany). The data consist of the MSCI World equity index and daily stock indices. The sample extends from September 1997 to September 2007. Vector autoregressive modeling applied on the index return time series is used as an econometric framework of analysis including the following techniques: Granger causality test, impulse response function and variance decomposition. The empirical findings indicate that the stock markets of Croatia, Estonia and Slovenia show considerable degree of financial integration with respect to the world market portfolio as well as to the three largest European stock markets, while on contrary the stock markets of Romania and Slovakia appear to be segmented relative to both, the world market and three major European stock markets. Furthermore, the results reveal a significant interdependence between Croatia and Slovenia, as well as a leading role of France and Estonia among investigated stock markets. In addition, a significant upward trend in stock indices of the European frontier emerging markets starting at the end of 2001 was observed. The results of this study suggest potential benefits from international portfolio diversification through investing in the frontier emerging markets in Europe. This study contributes to the existing literature by investigating one special subcategory of emerging markets, namely frontier emerging markets.
Keywords: frontier emerging market; financial integration; diversification benefits; fi=Finance and Accounting|; fi=Master's Degree Programme in Finance|